Refractive changes after lens-sparing vitrectomy for macular hole and epiretinal membrane - Muto T (Dove Medical Press, 2017)
Tetsuya Muto,1 Tomoharu Nishimura,1 Takefumi Yamaguchi,2 Makoto Chikuda,1 Shigeki Machida1 1Department of Ophthalmology, Dokkyo Medical University Koshigaya Hospital, Koshigaya, Japan; 2Department of Ophthalmology, Tokyo Dental College Ichikawa General Hospital, Ichikawa, Japan Purpose: Cataract progression after lens-sparing vitrectomy might differ according to original posterior segment diseases. Our objective was to analyze the refractive values after lens-sparing vitrectomy for macular hole (MH) and epiretinal membrane (ERM). Materials and methods: We reviewed the medical records of 25 MH patients (25 eyes) and 23 ERM patients (23 eyes) who underwent lens-sparing vitrectomy. Refractive changes in both groups were compared. All patients underwent 20-gauge three-port pars plana vitrectomy. Fluid–air exchange was performed during vitrectomy only in the MH group. The results were analyzed using the unpaired t-test, chi-square test, or Fisher exact probability test, and multivariate analysis. Results: There were no significant differences in the patient’s age (P=0.45). The myopia progression rate (D/month) was higher in the MH group after surgery than that in the ERM group (P=0.035). MH group had more females (P=0.043), longer surgical time (P<0.001), and higher frequencies of surgical adjuvants use (triamcinolone acetonide, P=0.019; brilliant blue G, P<0.001). The myopia progression rate in the MH group (R=0.568, P<0.001) correlated with female gender. However, no correlation was observed between longer surgical time and the use of surgical adjuvants. Conclusion: The rate of myopia progression was higher in the MH group. Fluid–air exchange and gender may affect the rate of myopia progression. Keywords: cataract, vitrectomy, macular hole, epiretinal membrane